Visible-Light-Driven Iodine-Catalyzed Synthesis of Unsymmetrical Disulfides via Oxidative Coupling - Ren, Ming-Zhe; Fu, Yan-Jun; Zhang, Bo-Sheng; Quan, Zheng-Jun; Wang, Xi-Cun (Synthesis, 2023)
Herein, a facile and environmentally friendly oxidative coupling reaction to obtain unsymmetrical disulfide compounds, without using metal or organic dyes as photocatalyst and only using a catalytic amount of iodine, was developed. Oxygen is used as oxidant in the reaction and the substrate scope is wide. A gram-scale synthesis also highlights the synthetic practicality of this photochemical strategy. Moreover, our mechanistic studies support the formation of disulfide products through free-radical coupling.
Keywords: iodine; visible light; sulfur; coupling; unsymmetrical disulfides